FRI0398 Derailed b cell homeostasis in patients with mixed connective tissue disease. (23rd January 2014) - Hajas, A.; Barath, S.; Szodoray, P.; Nakken, B.; Gogolak, P.; Szekanecz, Z.; Bodolay, E.
Abstract : Background: Mixed connective tissue disease (MCTD) is a systemic autoimmune disorder, characterized by the presence of antibodies to U1-RNP protein. Although the exact pathogenesis of MCTD is still unknown, B cell abnormalities characterized by autoantibody formation and polyclonal B cell activation play an important role. Objectives: The aim of the present study was to assess the peripheral B cell subsets in MCTD in the active and inactive stage of the disease, compared with healthy individuals. In order to evaluate the clinical relevance of these findings, the frequencies of B cell subsets were correlated with disease activity and autoantibody levels. Methods: Freshly drawn peripheral blood samples were obtained from 46 MCTD patients, and 20 age- and sex-matched healthy controls. Using anti-CD19, anti-CD27, anti-IgD and anti-CD38 monoclonal antibodies, the following B cell subsets were identified by flow cytometry: 1.transitional B cells (CD19+CD27-IgD+CD38high); 2.naive B cells (CD19+CD27-IgD+CD38low); 3.non-switched memory B cells (CD19+CD27+IgD+); 4.switched memory B cells (CD19+CD27+IgD-); 5.double negative (DN) memory B cells (CD19+CD27-IgD-) and 6.plasma cells (CD19+CD27highIgD-). Disease activity of MCTD was assessed by SLAM score. Results: The proportion of transitional B cells, naive B cells and DN B lymphocytes was higher in MCTD than in controls. Active, untreated MCTD patients had both elevated percentages and absolute numbers of CD19+CD27-IgD+CD38high transitional B cells, compared to the inactive stage (%: p<0.009; absolute number: p< 0.045). Both the relative and absolute number of naive B cells (CD19+CD27-IgD+CD38low) was higher in the active disease, than in the inactive stage (%: p< 0.002; absolute number: p<0.001). The distribution of CD27high plasma cells was significantly higher in patients with MCTD compared to healthy controls (p<0.001), while in the active stage, the proportion of CD27high plasma cells further increased (p<0.001). Positive correlation was found between the number of plasma cells and anti-U1RNP levels. The DN B cells were positive for CD95 surface marker. This memory B cells population showed a close correlation with disease activity (p<0.001). Conclusions: Several abnormalities were found in the peripheral B cell subsets in MCTD, which reinforces the role of derailed humoral autoimmune processes in the pathogenesis of MCTD. Disclosure of Interest : None Declared